Electroacupuncture Involved in Motor Cortex and Hypoglossal Neural Control to Improve Voluntary Swallowing of Poststroke Dysphagia Mice. (27th September 2020) - Cui, Shuai; Yao, Shuqi; Wu, Chunxiao; Yao, Lulu; Huang, Peidong; Chen, Yongjun; Tang, Chunzhi; Xu, Nenggui
Abstract : The descending motor nerve conduction of voluntary swallowing is mainly launched by primary motor cortex (M1). M1 can activate and regulate peripheral nerves (hypoglossal) to control the swallowing. Acupuncture at "Lianquan" acupoint (CV23) has a positive effect against poststroke dysphagia (PSD). In previous work, we have demonstrated that electroacupuncture (EA) could regulate swallowing-related motor neurons and promote swallowing activity in the essential part of central pattern generator (CPG), containing nucleus ambiguus (NA), nucleus of the solitary tract (NTS), and ventrolateral medulla (VLM) under the physiological condition. In the present work, we have investigated the effects of EA on the PSD mice in vivo and sought evidence for PSD improvement by electrophysiology recording and laser speckle contrast imaging (LSCI). Four main conclusions can be drawn from our study: (i) EA may enhance the local field potential in noninfarction area of M1, activate the swallowing-related neurons (pyramidal cells), and increase the motor conduction of noninfarction area in voluntary swallowing; (ii) EA may improve the blood flow in both M1 on the healthy side and deglutition muscles and relieve PSD symptoms; (iii) EA could increase the motor conduction velocity (MCV) in hypoglossal nerve, enhance the EMG of mylohyoid muscle, alleviate the paralysis of swallowing muscles, release the substance P, and restore the ability to drink water; and (iv) EA can boost the functional compensation of M1 in the noninfarction side, strengthen the excitatory of hypoglossal nerve, and be involved in the voluntary swallowing neural control to improve PSD. This research provides a timely and necessary experimental evidence of the motor neural regulation in dysphagia after stroke by acupuncture in clinic.